Accumulation of Heavy Metals in Potatoes Grown on Calcareous Soils of the Hamedan, Western Iran. Issue 4 (18th May 2016) - Jalali, Mohsen; Meyari, A.
ABSTRACT: This study was conducted to investigate heavy metal contamination in agricultural soils and their transfer in a soil-potato system. A total of 59 pairs of potato and soil samples, representing different locations were collected from Hamedan, western Iran and subjected to heavy metals analysis. Average concentrations of Cd, Cu, Fe, Mn, Ni, Pb, and Zn were 1.2, 13.1, 161.4, 13.2, 3.2, 19.5, and 41.5 mg kg −1 dry weight in potato tubers, respectively. A sequence of decreasing plant transfer factors values: Cd > Pb > Cu > Zn > Ni ≥ Mn > Fe was obtained. Furthermore, the health risk index (HRI) values were within the safe limit (<1) except for Cd and Pb. HRI values for Cd and Pb were higher than 1, indicating potential health risk, especially for children. The results indicated that daily intakes of Cd and Pb in potato in the study area may present a future hazard.